Human Immunodeficiency Virus (HIV) Type 1 Transframe Protein Can Restore Activity to a Dimerization-Deficient HIV Protease Variant - Dautin, Nathalie (American Society for Microbiology, 2003)
The protease (PR) from human immunodeficiency virus (HIV) is essential for viral replication: this aspartyl protease, active only as a dimer, is responsible for cleavage of the viral polyprotein precursors (Gag and Gag-Pol), to release the functional mature proteins. In this work, we have studied the structure-function relationships of the HIV PR by combining a genetic test to detect proteolytic activity in Escherichia coli and a bacterial two-hybrid assay to analyze PR dimerization. We showed that a drug-resistant PR variant isolated from a patient receiving highly active antiretroviral therapy is impaired in its dimerization capability and, as a consequence, is proteolytically inactive. We further showed that the polypeptide regions adjacent to the PR coding sequence in the Gag-Pol polyprotein precursor, and in particular, the transframe polypeptide (TF), located at the N terminus of PR, can facilitate the dimerization of this variant PR and restore its enzymatic activity. We propose that the TF protein could help to compensate for folding and/or dimerization defects in PR arising from certain mutations within the PR coding sequence and might therefore function to buffer genetic variations in PR.